Management of gout in older people. (12th February 2019) - Day, Richard O.; Lau, Wendy; Stocker, Sophie L.; Aung, Eindra; Coleshill, Mathew J.; Schulz, Marcel; Bechara, Jacob; Carland, Jane E.; Graham, Garry G.; Williams, Kenneth M.; McLachlan, Andrew J.
Abstract: Gout is an inflammatory musculoskeletal disorder with a prevalence of 1.6–6.8% in Australia. Gout is characterised by acute attacks of severe joint pain secondary to raised serum concentrations of uric acid and joint deposits of monosodium urate crystals. Recurrent attacks can affect quality of life and lead to irreversible joint damage. The prevalence of gout is increased in older people, and age‐related renal impairment, altered drug distribution and increased prevalence of comorbidities have significant consequences for safe and effective gout pharmacotherapy. For treatment of acute attacks in older people, dose reduction of colchicine may be needed due to renal impairment, and potential drug interactions require consideration. Use of non‐steroidal anti‐inflammatory drugs is limited by peptic ulceration, ischaemic heart disease, hypertension and renal impairment. Short courses of oral glucocorticoids may be preferable. For long‐term urate‐lowering therapy, allopurinol, probenecid and febuxostat are available in Australia. Lower starting doses of allopurinol are recommended in patients with renal impairment, but dose escalation to achieve target urate should follow. Concerns regarding increased cardiovascular risk with febuxostat are relevant to older patients. Despite the availability of effective therapy, gout remains undertreated, with maintenance of urate‐lowering therapy a major challenge. Education of patients and health professionals is essential to improve adherence to therapy. Abstract :